An NFκB Activity Calculator to Delineate Signaling Crosstalk: Type I and II Interferons Enhance NFκB via Distinct Mechanisms - Mitchell, Simon; Mercado, Ellen L.; Adelaja, Adewunmi; Ho, Jessica Q.; Cheng, Quen J.; Ghosh, Gourisankar; Hoffmann, Alexander (Frontiers in Immunology, 2019)
Nuclear factor kappa B (NFkB) is a transcription factor that controls inflammation and cell surivival. In clinical histology, elevated NFkB activity is a hallmark of poor prognosis in inflammatory disease and cancer, and may be the result of a combination of diverse micro-environmental constituents. While previous quantitative studies of NFkB focused on its signaling dynamics in single cells, we address here how multiple stimuli may combine to control tissue-level NFkB activity. We present a novel, simplified model of NFkB (SiMoN) that functions as an NFkB activity calculator. We demonstrate its utility by exploring how type I and type II interferons modulate NFkB activity in macrophages. Whereas type I IFNs potentiate NFkB activity by inhibiting translation of IkB and by elevating viral RNA sensor (RIG-I) expression, type II IFN amplifies NFkB activity by increasing the degradation of free IkB through transcriptional induction of proteasomal cap components (PA28). Both cross-regulatory mechanisms amplify NFkB activation in response to weaker (viral) inducers, while responses to stronger (bacterial or cytokine) inducers remain largely unaffected. Our work demonstrates how the NFkB calculator can reveal distinct mechanisms of crosstalk on NFkB activity in interferon-containing microenvironments.